2008
DOI: 10.2478/s11536-008-0026-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the wars in Croatia and Bosnia and Herzegovina on the incidence and outcome of singleton premature births in the Split University Hospital

Abstract: AbstractTo investigate the influence of the wars in Croatia and Bosnia and Herzegovina on incidence and perinatal outcome of singleton preterm births at the Department of Gynecology and Obstetrics in the Split University Hospital. Data were collected by reviewing patients’ files at the Department of Gynecology and Obstetrics from three periods: the three years before the war (1988–1990), during the war (1992–1994), and after the war (1996–1998). A total of 2,358 patients’ files… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“… 28 31 38 The Pavlinac et al study even showed significant decreases in the overall rates of stillbirth among all singleton births. 33 This study also demonstrates that there was a significant increase in stillbirths among mothers who had preterm births (p<0.001)(see online supplementary appendix table 2 ).…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“… 28 31 38 The Pavlinac et al study even showed significant decreases in the overall rates of stillbirth among all singleton births. 33 This study also demonstrates that there was a significant increase in stillbirths among mothers who had preterm births (p<0.001)(see online supplementary appendix table 2 ).…”
Section: Resultssupporting
confidence: 55%
“…In contrast, one study with a low risk of bias compared with the other included studies found an increase in post-term births in Somalian women 39 exposed to armed conflict and another study showed a significant decrease in the number of premature deliveries during the war. 33 However, Pavlinac et al 33 found that within the population of premature babies both stillbirth and early neonatal mortality rates increased during the period of armed conflict. The other studies found no such significant relationship between armed conflict and prematurity 28 37 (see online supplementary appendix table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies point to changes in services provision or uptake as potential drivers of adverse neonatal health outcomes in conflict settings. Evidence from the Syrian refugee context and Croatia found decreased access to antenatal care and skilled childbirths during conflict [8,9]. A recent study found an association between conflict and decreased cesarean section rates in the oPt [10].…”
Section: Introductionmentioning
confidence: 99%
“…This includes often patchy information about pregnancy histories in many countries, leading most research to focus on pregnancy outcomes related to live births, and, hence, relying on selected samples. A recent systematic review could find only a few analyses of the associations between conflict exposure and miscarriages (2 studies), stillbirth risk (5 studies), and perinatal mortality (2 studies) [14][15][16][17][18][19][20]. All these studies are observational and suffer from data and/or methodological limitations that make causal inference difficult [13] (fAU : Pleasenotethattextfootnotesarenotperm ive studies are before-and-after analyses without an adequate statistical control for observable and unobservable confounders [14][15][16][17]19].…”
Section: Introductionmentioning
confidence: 99%